A Two-Level Problem Solving Practicing Approach using a Location Based App - Castro, Thais; Castro, Alberto; Castro, Liliane; Soares, Marcos; Gadelha, Bruno (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2016)
Mastering problem solving reasoning is an important skill for computing students. In order to acquire this ability, students might use a collaborative approach and work in groups, getting explanations about problems solved in the past, discussing advantages and disadvantages of specific choices, taking into account different points of view. This paper presents a two-level approach for practicing problem solving skills. In this approach, different computing students enrolled in two courses practice their collaborative problem solving skills in distinct ways. Those students enrolled on the most advanced course develop apps for the freshmen enrolled in the introductory course. These freshmen students learn to solve basic logic problems as part of their course. An exploratory case study was conducted in order to observe and evaluate how students interact in groups developing or using the app.